(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: Analyze factors affecting adherence to antiretroviral therapy (ARV) of HIV-infected people being treated at the HIV/AIDS Clinic, Tra Vinh Provincial General Hospital in 2024. Research method: Using a qualitative research design combined with quantitative. Selecting a sample of all 305 patients over 18 years old and treated for over 12 months who are on ARV treatment at the Clinic in 2024. Collecting data from May to October 2024, quantitative interviews after patients receive medication on the day of re-examination, 11 in-depth interviews with medical staff, patients and their families. Results: Age group over 40, using health insurance, knowledge about treatment, family support, counseling and positive attitude of medical staff positively affect treatment adherence. Long waiting times, drugs not being prescribed for many months, alcohol and drug use, and side effects of drugs negatively affect treatment compliance. Conclusion: Treatment facilities need to strengthen solutions related to improving medical examination and treatment processes, ensuring drug reserves to be able to dispense drugs for many months to eligible groups, have solutions to support patients with health insurance card interruptions, and apply tools to remind patients to take medication and return for check-ups on time.